TAMPING TOOLS MANUFACTURING BY OPEN MOULD FORMING - Akpolat, Hasan; Sezek, Sinan; Aksakal, Bünyamin (ModTech Publishing House, 2025)
Balancing of railways is very important for transport and safety. Tamping tools, picks, are balancing tools used together with Tamping machines. The production of these tools, which are used in an average of 12000 pieces per year, is very important for the national economy. From this point of view, the moulds required for the production of compaction tools used in the correction of railways were designed and analyzed. For this purpose, a closed mould of 41Cr4 steel was designed and selected for shaping the compaction tool, and FEA was carried out. Two moulds were modelled for the body connection and shovel parts. The pressing process temperature was determined as 600oC, and the required pressing force was determined to be 250 MPa from FE analysis to minimize the effect of temperature on the microstructure. In FE analysis, parameters such as stress, strain, temperature, and metal flow were examined, and the highest stress value in the pressing process of the sphere part was found to be approximately 705 MPa at 30% deformation, and the maximum effective plastic strain was determined as 1.88 at 70% deformation. The temperature change was 684oC in the forming of the body part and 647oC in the forming of the sphere part. Metal flow was recorded as 271 mm/s at a 30% deformation value, where the maximum deformation occurred, and 135 mm/s in the shaping of the sphere part. The first stage for the production of tamping tool inserts, the pressing method in closed moulds, has been completed and presented in the literature. © 2025, ModTech Publishing House. All rights reserved.
Keywords: closed die forming; FEA; steel; Tamping tools